KEPENTINGAN INDONESIA BEKERJASAMA DENGAN BELANDA DALAM BIDANG PERTAHANAN TAHUN 2013-2014 - Sharaswaty Karyono; Ahmad Jamaan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research aims to explain about Indonesia’s interest in Indonesian - Netherland defense partnership. This partnership held because Indonesia has a lack defense in army defense and army technology (Alutsista). Indonesia need to increase and modernized its army defense to protect Indonesia’s territory from traditional threat and non-traditional threat.In this research, the writer uses rational choice theory. Rational choice theory is is used to analyze the purpose of state, to analyze cost and benefi from the choice that a state has made to keep its interest. The support theory is strategy and security theory about “confrontation strategy”. Indonesia – Netherland defense partnership held because of the threat to Indonesia and to increase its power in army defense.Indonesia has been having defense partnership with advanced countries, such as: United States, Germany, Russia, South Korea, England, Spain, France, and others. Therefore, Indonesia decided to do defense partnership with Netherland. Indonesia gain its interest to modernized army technology system (Alutsista) and increase its army defense.Key words: interest, partnership, defense, Alutsista, Netherland.